Small scale Coffee Farmer’s Response towards Management of Coffee Pest through Field Level Techniques - Panthi, Bhanu Bhakta (Journal of Institute of Science and Technology, 2015)
Coffee among the Nepalese farmers is one of the breaks-through from the traditional subsistence food crops to agrobased industrial crop. It was planted under multi cropping pattern with fruits species; Musa paradiciaca L (banana), Citrus lemon (Lemon), Artocarpus heterophyllus (jack fruit), Pyrus pyrifolia (pear), and Psidium guajava L (guava), fodders species, cereals and vegetables. Coffee farmers of Gulmi and Lalitpur tried to manage the orchards through shade management, intercropping, optimum manuring, and protection from pests. For this, farmers adopted various management techniques; handpicking and destroying, use of local pesticides, use of pheromones trap. More than 90 % of the coffee farmers were used local pesticides but with random composition and amount. Most preferred botanicals at farmer’s level are; Allium sativum L., Allium cepa L., Azadirachta indica, Eupatorium adenophorum, Utrica dioca L. Artemesia indica, Zanthoxylum Zanthoxylum. Though, these techniques were applied, farmers still were not successful fully to overcome the problem of White Stem Borer (Xylotrechus quadripes). This might be due to untimely application and not proper composition to prepare in large quantity. This prepared pesticide was only effective to control small and soft bodied insects. The using of botanicals was observed to reduce the chances of pest attack and found a significant step toward green pesticides. Journal of Institute of Science and Technology, 2014, 19(2): 37-44